GE_GERICHTE A/677/2009 vom 18. November 2008 - GE Cour de justice (2008)
; PC ; OPPOSITION(PROCÉDURE) ; FORME ET CONTENU ; SIGNATURE ; FORMALISME EXCESSIF ; CONDITION DE RECEVABILITÉ | LPGA 60; LPGA 52; OPGA 10;